Analysis of Allama Iqbal’s Poetry “Kabhi Ae Haqeeqat E Muntazir” Under The Light of Eugene Nida’s Linguistic Model - Zahra, Khushbakht (English Lecturers and Teachers Association (ELTA), 2024)
This study examined Allama Iqbal’s poem “Kabhi Ae Haqeeqat-e-Muntazir” through Eugene Nida’s dynamic equivalence model, evaluating Dr. Mustansir Mir’s English translation against the original Urdu text. The analysis revealed a nuanced interplay between literal meaning and metaphorical expression, highlighting challenges in conveying cultural nuances. The Findings indicated that Mir’s translation adeptly preserves the essence of Iqbal’s profound themes—encompassing the quest for truth, the transcendent power of music, the soul’s significance, sacrifice, peace, and sincerity in prayer. By navigating linguistic complexities and cultural barriers, the translation succeeds in ensuring accessibility and cultural resonance for a wider audience, affirming Nida’s principles in maintaining fidelity to the original while adapting it to a different linguistic and cultural milieu. Keywords: Dynamic Translation; Nida’s Linguistic Model; Iqbal’s Poetry